Highly efficient synthesis of phytosterol linolenate in the presence of Bronsted acidic ionic liquid. (15th October 2018) - He, Wen-Sen; Li, Ling-Ling; Huang, Qiu-Jin; Yin, Ji; Cao, Xue-Chen
Highlights: Phytosterol esters were firstly synthesized using Bronsted acidic IL as catalyst. The synthesized products were characterized by TLC, FT-IR and MS. The conversion of phytosterols could reach above 96% for 30 min Abstract: Phytosterols are effective in reducing plasma cholesterol. However, phytosterols in a free form have some disadvantages because they have a high melting point and a poor oil solubility, thereby limiting their practical application in foods. The present study was to establish a green and highly efficient method to synthesize phytosterol linolenate for the first time by employing Bronsted acidic ionic liquid (IL) as a catalyst in order to improve its oil solubility. The product was separated, analyzed and subsequently characterized using thin layer chromatography, fourier transform infrared spectroscopy and mass spectroscopy. The conversion of phytosterols could reach above 96% in a very short time (30 min) under the following optimum conditions: 3% 1-butylsulfonate-3-methylimidazolium trifluoromethanesulfonate ([BSO3 HMim]OTf) as a catalyst, 110 °C and 1:1.75 M ratio of phytosterols to ethyl linolenate. The present method demonstrated that [BSO3 HMim]OTf would be a potential catalyst for phytosterol ester synthesis. Most importantly was that the oil solubility of phytosterol linolenate was much greater than its corresponding free phytosterols.